2015
DOI: 10.1259/bjr.20150175
|View full text |Cite
|
Sign up to set email alerts
|

Carotid and vertebral artery stenosis evaluated by contrast-enhanced MR angiography in nasopharyngeal carcinoma patients after radiotherapy: a prospective cohort study

Abstract: Radiation-induced CA and VA stenosis exists widely in patients with NPC after radiotherapy, and its prevalence is more common in patients with older age and longer interval from radiotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 31 publications
1
25
1
Order By: Relevance
“…One study evaluated carotid stenosis of NPC patients by using contrast-enhanced MR angiography scanning. They found a rate of 37.5%, which is higher than our finding 19 . The difference may be attributed to different measurement methods as was discussed by the authors.…”
Section: Discussioncontrasting
confidence: 86%
See 1 more Smart Citation
“…One study evaluated carotid stenosis of NPC patients by using contrast-enhanced MR angiography scanning. They found a rate of 37.5%, which is higher than our finding 19 . The difference may be attributed to different measurement methods as was discussed by the authors.…”
Section: Discussioncontrasting
confidence: 86%
“…The present study illuminated that an older age might relate to a higher incidence of stenosis (≥50%) in NPC patients after RT treatment, consistent with the results of Zhou et al . 19 . They also found that the risk rose with time after RT.…”
Section: Discussionmentioning
confidence: 99%
“…Imaging modality used for the detection of carotid stenosis was Doppler Ultrasound (DUS) in all studies except that by Dupin et al and Zhou et al, which used magnetic resonance imaging. 27,39…”
Section: Characteristics Of the Included Studies And Patientsmentioning
confidence: 99%
“…9) Lam et al 14) evaluated vascular stenosis using ultrasonography after radiotherapy for head and neck tumors and reported that 50% or severer carotid artery stenosis was observed in 29.6% of the patients but that vertebral artery stenosis was rare, being noted in only 5.6%. On the other hand, Zhou et al 15) evaluated the presence or absence of vascular stenosis using contrast-enhanced MRA in 72 patients 3 years or longer after radiotherapy for nasopharyngeal cancer and reported that 50% or severer carotid artery stenosis was noted in 37.5% and that vertebral artery stenosis was noted in 34.7%, suggesting that the latter is not a rare condition. While the common carotid artery stenosis is a frequent inserting three Hydrosoft 4 mm × 10 cm (Terumo Corporation, Tokyo, Japan), three Hydrosoft 3 mm × 10 cm, and one 2.5 mm × 6 cm coils (Fig.…”
Section: Case Presentationmentioning
confidence: 99%